Transforming Bale Twine into Useful Products with an Affordable Melting Machine: Closed-Loop for Recycling Plastics - Akesh Babu Kakarla; William Ritchie; Ing Kong (Recycling)
The escalating use of plastic materials in agricultural practices has substantially increased the amount of plastic waste directed to landfills, leading to significant environmental and ecological challenges. Conventional disposal methods have been found to release hazardous pollutants, including microplastics and toxic chemicals, exacerbating these concerns. This study aims to address the environmental impact of agricultural plastic waste by exploring advanced reprocessing technologies and characterising the processed waste to assess its physical, mechanical, and thermal properties. Synthetic polymer-based bale twine (BT) waste, commonly used in livestock farming, was processed using an economically viable melting machine developed by Ritchie Technology. The BT and processed bale twine (PrBT) were analysed to understand their properties. Fourier transmission infrared spectroscopy revealed that the waste primarily consisted of polypropylene (PP). Thermal analysis indicated that the melting temperature of the PrBT was 162.49 °C, similar to virgin PP. Additionally, tensile testing revealed that the PrBT had an ultimate strength of 13.06 MPa and a Young’s modulus of 434.07 MPa. The PrBT was further transformed into a bench that can be applicable in outdoor applications. Furthermore, the PrBT was extruded into 3D printable filament. Therefore, it is evident that bale twine waste can be given a second life through an economically viable technology.